2013
DOI: 10.1371/journal.pone.0056888
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Oral and Enteric Campylobacter concisus Strains on Expression of TLR4, MD-2, TLR2, TLR5 and COX-2 in HT-29 Cells

Abstract: Campylobacter concisus, a Gram-negative bacterium that colonizes the human oral cavity, has been shown to be associated with inflammatory bowel diseases (IBD). The effects of different C. concisus strains on intestinal epithelial expression of Toll like receptors (TLR) have not been investigated. This study examined the effects of C. concisus strains isolated from patients with IBD and controls on expression of TLR4, its co-receptor myeloid differentiation factor (MD)-2; TLR2, TLR5, cyclooxygenase-2 (COX-2) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 50 publications
3
29
0
Order By: Relevance
“…Previous studies found that some oral C. concisus strains or their toxins were able to damage the intestinal epithelial barrier and induce intestinal epithelial production of proinflammatory cytokines using cell line models111213. These data suggest that translocation of enteric virulent C. concisus strains from the human oral cavity to the intestinal tract may cause enteric diseases in some individuals.…”
mentioning
confidence: 66%
“…Previous studies found that some oral C. concisus strains or their toxins were able to damage the intestinal epithelial barrier and induce intestinal epithelial production of proinflammatory cytokines using cell line models111213. These data suggest that translocation of enteric virulent C. concisus strains from the human oral cavity to the intestinal tract may cause enteric diseases in some individuals.…”
mentioning
confidence: 66%
“…In addition to IBD, C. concisus was frequently isolated from diarrheal stool samples, suggesting its involvement in diarrheal disease (Lindblom et al, 1995; Lastovica, 2006; Kalischuk and Inglis, 2011; Nielsen et al, 2013). Some oral C. concisus strains were found to invade human intestinal epithelial cells, further supporting the idea that they can cause enteric disease (Nielsen et al, 2011; Ismail et al, 2012, 2013). Various virulence factors were found in C. concisus , such as the zonula occludens toxin (Zot), which was shown to cause prolonged damage to the intestinal epithelial barrier, increase and enhance the response of macrophages to other bacterial species (Mahendran et al, 2013, 2016; Liu et al, 2016).…”
Section: Introductionsupporting
confidence: 52%
“…Both oral and enteric C . concisus strains have been shown to induce the production of IL-8 in HT-29 cells [13,14,15]. Some oral C .…”
Section: Introductionmentioning
confidence: 99%
“…Some oral C . concisus strains isolated from patients with IBD were found to be invasive to Caco 2 cells and more effective in upregulating surface expression of Toll like receptor 4 in HT-29 cells [12,15]. Furthermore, increased intestinal epithelial apoptosis and permeability by some C .…”
Section: Introductionmentioning
confidence: 99%